Isolation And Characterization Of Α–L-Rhamnosidase Producing Bacterium, Agrococcus Sp. Bkd37, From A Warehouse Soil And Partial Optimization Of Its Culture Conditions (Applied Biological Research, 2020)
The present study was attempted to identify and partially optimize the culture conditions of a potential α-L-rhamnosidase producing bacterium isolated from warehouse soil of Dibrugarh, Assam (India). Twenty eight bacterial strains were isolated and the isolate BKD37 showed maximum  rhamnosidase enzyme activity (10.01 ± 0.001 U mL-1) in crude culture  medium. The 16S rRNA gene sequencing and phylogenetic analysis of  BKD37 strain showed maximum similarity with that of Agrococcus sp. The  culture conditions of strain BKD37 for the production of extracellular  rhamnosidase enzyme was partially optimized in a basal medium in shake  flask. The maximum rhamnosidase production was achieved after 60 h  incubation at 30oC and pH 6.0. The rhamnose and NH4NO3 were found to  e the best carbon and nitrogen sources, respectively, in basal medium for  α-L rhamnosidase enzyme production.
Keywords: Agrococcus sp; α-L-rhamnosidase; bacterium; characterization; warehouse soil